Privación del sueño y su influencia en la atención selectiva de los internos de medicina de los Hospitales Isidro Ayora y Manuel Ygnacio Montero de la ciudad de Loja. - Enríquez Calderón, Edison Vladimir (2017)
Sleep quality not only refers to sleeping well, but also includes a good daytime functioning, and poor quality can affect different threads of care. Besides medical interns are vulnerable to changes in their quality of sleep causing a shortfall in mental health because of its many academic and work activities. Therefore the research study called Sleep Deprivation and their influence on selective attention of internal medicine hospital Isidro Ayora and Manuel Montero Ygnacio city of Loja was developed; The objectives of this research were to evaluate the quality of sleep that present internal medicine, verify selective attention and relate sleep quality and selective attention. This study was type descriptive cross where 70 medical interns, whom I were administered the questionnaire Quality Index Dream of Pittsburgh and the Trail Making Test, the following results participated: 100% (n = 70) of the inmates were poor sleepers and presenting a poor sleep quality, 57.1% (n = 40) of the inmates presented a deficit in selective attention. It was concluded that the poor quality of sleep is more prevalent in the threads with greater involvement of cortico-cortical circuits (selective and divided attention). minor difficulties in sustaining attentional were found. Keywords: sleep deprivation, medical interns, selective attention, quality of sleep.